An expert system for technological disasters management- Malaysian case - Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed; Ismail, Norhafizah (2011)
Disasters globally are often classified according to their speed of onset which is slow or sudden, or according to their cause either natural or man-made. Disasters may take many forms, and occur as a result of one or more wide range of events, both natural and man induced. The duration of these events may range from a few seconds to many years. Malaysia has started its industrialization development in order to be a fully developed and industrialized country by the year 2020. Malaysia also has experienced several disasters due to the rapid industrialization. To achieve the advantages from the industrialization, the negative consequences must be eliminated, reduced or controlled. This research has studied, reviewed and analyzed the man-made disaster from 1991-2009 in form of technological disasters, which occurred in Malaysia AND resulted in 1649 death and injured 1934. The management for the mentioned period has been developed by an Expert System (ES) that used as a tool in managing man-made technological disaster.